Maternal level of education, maternal type of occupation, and the provision of complementary feeding - Anafrin Yugistyowati; Maulia Marza (Alma Ata University Press, 2017)
ABSTRACTBackground: Complementary Feeding is an additional food or drink containing nutrients, given to infants or children aged 6-24 months to meet nutritional needs other than breast milk. Provision of Complementary Feeding was given from age 6 to 24 months as the age increase, and children then need more nutrients grow.Objectives: To know the relationship between education level and mother’s type of work with the practice of giving of baby milk at 6-24 months in Sedayu Bantul, Yogyakarta.Methods: This was an observational research using analytical survey method with cross-sectional approach. Research subjects were mothers who have babies aged 6-24 months. Sampling technique using stratified random sampling with a number of respondents 287 under 2 years children in Sedayu I and II Bantul Yogyakarta. Data collection was using questionnaires and checklist sheets.Results: The result of statistical test using Chi-Square showed that there was a correlation between maternal education level and the practice of giving was breast milk in Sedayu I and II Bantul Health Center, with result p = 0,000 <0,05. There was a relationship between the type of mother’s work with the practice of giving the Complementary Feeding at Sedayu I and II Bantul Health Center, with result p = 0,003 <0,05. The closeness of the relationship between the level of education and the type of work of the mother with the practice of giving the Complementary Feeding is categorized as low with the value of 0.282 and 0.199.Conclusions: There was a correlation between the level of education and the type of work of the mother with the practice of giving Complementary Feeding in Sedayu I and II Bantul Yogyakarta.KEYWORDS: education level, job type, practice of complementary feeding